An investigation of shock wave therapy and low‐intensity pulsed ultrasound on fracture healing under reduced loading conditions in an ovine model. Issue 3 (11th August 2017) - Gadomski, Benjamin C.; McGilvray, Kirk C.; Easley, Jeremiah T.; Palmer, Ross H.; Jiao, Jian; Li, Xiaofei; Qin, Yi‐Xian; Puttlitz, Christian M.
ABSTRACT: The use of shock wave therapy (SWT) and low‐intensity pulsed ultrasound (LIPUS) as countermeasures to the inhibited fracture healing experienced during mechanical unloading was investigated by administering treatment to the fracture sites of mature, female, Rambouillet Columbian ewes exposed to partial mechanical unloading or full gravitational loading. The amount of fracture healing experienced by the treatment groups was compared to controls in which identical surgical and testing protocols were administered except for SWT or LIPUS treatment. All groups were euthanized after a 28‐day healing period. In vivo mechanical measurements demonstrated no significant alteration in fixation plate strains between treatments within either partial unloading group. Similarly, DXA BMD and 4‐point bending stiffness were not significantly altered following either treatment. μCT analyses demonstrated lower callus bone volume for treated animals (SWT and LIPUS, p  < 0.01) in the full gravity group but not between reduced loading groups. Callus osteoblast numbers as well as mineralized surface and bone formation rate were significantly elevated to the level of the full gravity groups in the reduced loading groups following both SWT and LIPUS. Although no increase in 4‐week mechanical strength was observed, it is possible that an increase in the overall rate of fracture healing (i.e., callus strength) may be experienced at longer time points under partial loading conditions given the increase in osteoblast numbers and bone formation parameters following SWT and LIPUS. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:921–929, 2018.